Eleven Reasons for Adaptation of Swedish Parenting Programs - Pettersson, Kristoffer; Liedgren, Pernilla; Giannotta, Fabrizia; von Thiele Schwarz, Ulrica (Frontiers in Health Services, 2022)
While questions about adaptation and fidelity are of great concern in many implementation projects, less attention has been paid to reasons for adaptations that remain when evidence-based interventions (EBIs) are used in clinical and community settings. This study aims to explore reasons for adaptations that can arise when using parenting programs in a community setting. Seventeen individual interviews with providers were conducted and analyzed thematically, resulting in 11 reasons for adaptations organized into four separate areas: characteristics of group leaders (supplementary skills and knowledge, preferred ways of working), characteristics of families (problem complexity, diverse or limited educational experience, non-parenting needs for support, colliding value systems), group incidents (criticism and challenges, excessive questions or discussions), and didactic challenges (lack of focus or engagement, limitations of the material, language differences). The study shows that factors triggering adaptation and fidelity decisions continuously reappear in the provision of parenting programs in community settings. Knowledge about reasons for adaptation can be used to inform decision-making during implementation planning, as well as the sustainment of implemented interventions.